New Recurrent Structural Aberrations in the Genome of Chronic Lymphocytic Leukemia Based on Exome-Sequencing Data - Mosquera Orgueira, Adrián; Antelo Rodríguez, Beatriz; Díaz Arias, José Ángel; González Pérez, Marta Sonia; Bello López, José Luis (Frontiers in Genetics, 2019)
Chronic lymphocytic leukemia (CLL) is the most frequent lymphoproliferative syndrome in western countries and it is characterized by recurrent large genomic rearrangements. During the last decades, array techniques have expanded our knowledge about CLL’s karyotypic aberrations. The advent of large sequencing databases expanded our knowledge cancer genomics to an unprecedented resolution, and enable the detection of small scale structural aberrations in the cancer genome. In this study, we have performed exome-seq based CNA and LOH analysis in order to detect new recurrent structural aberrations. We describe 54 recurrent focal CNAs enriched in cancer-related pathways, and their association with gene expression and clinical evolution. Furthermore, we discovered recurrent large copy number neutral LOH events affecting key driver genes, and we recapitulate most of the large CNAs that characterize the CLL genome. These results provide “proof-of-concept” evidence supporting the existence of new genes involved in the pathogenesis of CLL.